Study pressure and self harm in Chinese primary school students: the effect of depression and parent-child relationships - He, Jing-Lan; Xu, Xiao-Ming; Wang, Wo; Chen, Jian-Mei; Zhang, Qi; Gan, Yao; Cao, Jun; Ding, Da-Qin; Hu, Jin-Hui; Chen, Xiaorong; Kuang, Li (Frontiers in Psychiatry, 2025)
BackgroundSelf-harm has become a significant and increasing global problem in children and adolescents. In this study, we tested a moderated mediation model to examine the impact of study pressure and depression, and one protective factor, good parent-child relationship, on self harm.MethodsA self-report Questionnaire survey was conducted among 33,285 primary school students from 3rd-6th grade (mean age = 10.36 years, SD = 1.24, 51.7% girls) in Shapingba District Chongqing, China. The survey assessed study pressure, depression, parent-child relationship, and self harm behaviors.ResultsThe reporting rates of self-harm and depression in grades 3-6 of primary school were 12.7% and 16.3%, respectively. Both moderate and high study pressure were significantly associated with an increased risk of self-harm, with depression acting as a mediator (indirect effects: moderate study pressure = 0.045, high study pressure = 0.125, p < 0.001). Furthermore, a good parent-child relationship weakened the association between study pressure and self-harm, thus self harm on moderate study pressure (β=-0.057) and on high study pressure (β=-0.032) are lower than those without the moderator of a good parent-child relationship(β=0.116; β=0.168), as well as between study pressure and depression.ConclusionsThis study is the first to conduct a self-harm survey in the largest population-based sample of Chinese primary school students. The results highlight the importance of monitoring study pressure, fostering a positive parent-child relationship, and managing depressive symptoms to support students’ mental health. These findings enhance our understanding of the development of self-harm behaviors and can inform the design of targeted intervention programs aimed at reducing self-harm among primary school students.